Clinico- Biochemical Profile of Neonatal Seizure - Shah, GS; Singh, MK; Budhathoki, S; Kalakheti, BK; Baral, DD (Journal of Nepal Paediatric Society, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Objectives: The present study was undertaken to study the incidence, etiological factor, and days of onset, clinical types and biochemical abnormalities in babies having neonatal seizures. Materials and Methods: This is a retrospective, observational hospital based study. Ninety neonates, who developed seizures before 28 days of life and admitted to neonatal intensive care unit and nursery with neonatal seizure, were evaluated for incidence, etiological factor, clinical types and biochemical abnormalities found in neonatal seizure. The variables were analysed using Chi- Square and student t- test. Results: The incidence of neonatal seizure was 10.3/ 1000 live births. The seizures were common in male babies. 65 (72.2%) neonates were born to multiparous women while 35 (38%) were born to primigravidas. In birth asphyxia (n= 40), the most common type of seizure observed was subtle seizure 20 (50%), followed by focal clonic 10 (25%) and multifocal clonic 5 (12.5%). Tonic type of seizure was observed in 3 (7.5%) and myoclonic in 2 (5%). Meningitis and septicaemia was the second most common cause of neonatal seizure observed in our study. Among metabolic abnormalities hypoglycaemia was found in 20 (22%) and hypocalcaemia in 10 (11%). Conclusion: The commonest cause of seizure was birth asphyxia presenting within 72 hours of life. Among infection septicaemia and meningitis was the most common cause leading to neonatal seizure. Among biochemical abnormalities the most common cause of seizure observed in our study was hypoglycaemia and hypocalcaemia. Subtle seizures were the commonest type of seizure observed in this study. Key words: Neonatal seizure, biochemical disturbances in seizure. DOI = 10.3126/jnps.v28i1.1398 J. Nepal Paediatr. Soc. Vol.28(1) p.7-9